Global patterns of mainland and insular pollination networks. Issue 7 (8th September 2015) - Traveset, Anna; Tur, Cristina; Trøjelsgaard, Kristian; Heleno, Ruben; Castro‐Urgal, Rocío; Olesen, Jens M.
Abstract: Aim: Interaction networks are being increasingly used to evaluate macroecological patterns. We explored a global dataset to identify differences in the structure of pollination networks from islands (of oceanic and continental origin) and mainlands. For oceanic islands, we further evaluated the effects of key island traits on network structural parameters. Location: Fifty‐two quantitative plant–pollinator networks from continental islands ( n  = 23), oceanic islands ( n  = 18) and mainlands ( n  = 11) located world‐wide. Methods: The effect of geographical origin upon network structure was explored by means of generalized mixed models, accounting for biogeographical region, sampling intensity, latitude and network size. For oceanic island networks, the influence of area, age, elevation and isolation was also evaluated. Results: The structure of pollination networks was fairly consistent between mainland and continental islands and only a few differences were noted. Oceanic island networks, however, were smaller and topologically simplified, showing a lower interaction diversity, and higher plant niche overlap than mainland and continental island networks. Isolation and elevational range of oceanic islands influenced the total number of species and interactions. Networks from higher‐elevation oceanic islands were less nested and those located towards the equator exhibited higher interaction richness. Island area showed no significant effect on any of the network metrics studied here. Main conclusions: Pollination networks appear structurally similar regardless of their geographical origin. However, networks from continental islands are more similar to their mainland counterparts than to those from oceanic islands, probably due to the geological nature of continental islands, which are fragments of the mainland to which they were once connected. Oceanic island networks are the least species‐ and link‐rich, and exhibit the lowest interaction diversity and the highest plant niche overlap, possibly due to lower pollinator richness. The most isolated and low‐elevation islands show the simplest networks, and are thus probably the most vulnerable to pollination disruptions.